Study of the relationship between urbanization and environment in the Jiulong river basin based on coupling coordination degree model - Liao, Yiping; Liu, Guangsheng; Luan, Haijun; Deng, Guojiang; Zheng, Meiduan; Cai, Wenhao (Frontiers in Environmental Science, 2023)
Rapid urbanization has placed the sustainable development of some watershed ecosystems in jeopardy. To achieve sustainable urban development, it is vital to identify the coupling mechanisms between urbanization and the quality of the ecological environment. In this study, we established indicators to evaluate the urbanization and ecological environment systems in the Jiulong River Basin. These were used to analyze spatial and temporal changes and build a coupling coordination degree model. Using this, we investigated the level of development coordination between urbanization and the ecological environment quality in the basin. Our data sources included nighttime lighting and Landsat data obtained from 2000 to 2020. The findings indicate the following. (1) Urbanization levels in the basin have been rising annually, and the years 2010 to 2020 represent a stage of high urbanization growth. In addition, the development levels are spatially heterogeneous, with high levels in the south and low levels in the north. (2) The ecological environment quality category for the basin is generally Excellent; however, many facets of the climate and human activity drastically lowered this grade in 2005. (3) In the basin, there is a Basic Coordination relationship between urbanization and environmental quality, but the number of cities falling into the Moderate Imbalance category has been growing. (4) Increasing the level of urbanization improves the coordination between urbanization and the ecological environment more than improving environmental quality, but antagonistic effects make it necessary to strengthen the protection of the ecological environment alongside economic development. From the viewpoint of counties, this study examined the long-term interactions between the ecological environment and urbanization in Fujian Province, China. Recommendations for ways in which to balance urban development and environmental concerns in coastal watersheds are presented, providing references that the future of development of this area of China can be sustainable.